Contactless service encounters among Millennials and Generation Z: the effects of Millennials and Gen Z characteristics on technology self-efficacy and preference for contactless service. Issue 1 (9th November 2021) - Kim, Songmee; Jang, Seyoon; Choi, Woojin; Youn, Chorong; Lee, Yuri
Abstract : Purpose: "Contactless service" refers to the use of technology in providing products or services without a salesperson. This study explores the mechanism underlying Millennial and Generation Z (M/Z generations) consumers' preference for contactless service over salespersons in retail stores. In addition, this study tests differences between the M/Z generations. Design/methodology/approach: The researchers predict characteristics to be antecedents of young consumer's preference for contactless service over salespersons and that the effects are mediated by technology self-efficacy. Next, a moderating variable (perceived consumer conformity) is added in the path between technology self-efficacy and the preference for contactless service. The hypotheses are tested among 142 Gen Z and 137 Millennial respondents. Findings: The results show that M/Z generations' characteristics significantly influence the preference for contactless service, except for security seeking. Also, interests in new technology and safety seeking are perceived higher by M/Z generations. The influence of technology self-efficacy on the preference for contactless service is moderated by social conformity. Originality/value: As retail technology rapidly develops, the service industry is expected to change from the past, where salespersons played an important role, to contactless services. This study has academic and practical values, for the authors clarify the underlying psychological mechanisms of why young consumers prefer retail technology rather than communication with salespersons.